Diabetic patients’ journey in healthcare: a multi-method, multi-center study proposal - ÇİFÇİLİ, SALİHA SERAP; SUR ÜNAL, ÜLKÜ (My University, 2022)
Background: Diabetes Mellitus (DM) requires patients to adhere to several treatments, diagnostic examinations and admit to different health professionals. Thus patients face a complicated journey through the healthcare system. This journey might be affected by factors such as socio-cultural characteristics and healthcare services. One of the core competencies of family medicine, continuity of care, stands as a cornerstone to guide the patients in this complicated journey and is associated with decreased emergency department attendance, hospitalization, and mortality. Research questions: How can we describe diabetic patients’ journey in health systems with different integration levels by using existing data and operational research methods? How is this journey experienced by the patients? Does continuity of care facilitate this journey? Method: This multi-method, multi-country study will include adult patients with type 2 DM. Patients will be recruited by primary care physicians from participating countries by purposive sampling to ensure maximum variability in terms of age, literacy, gender and diabetes age. The quantitative part will be conducted as follows. Data will be retracted from electronic medical records. Process mining will be applied to describe the paths of patients in the system. This method uses event logs to describe the processes, check conformance to defined processes and analyze processes by defining cycle and waiting times at various stages and identifying bottlenecks. Stastistical analysis will be performed via R package. The level of continuity of primary care will be calculated using the Usual Provider Continuity index in which the numerator is the number of visits with “own” physician for a year and the denominator is the total number of visits with other physicians for the same year. The qualitative part will explore the behaviour and experiences of patients in their regular interactions with primary care physicians. For this, a phenomenological approach using semi-structured interviews is proposed.
Keywords: Tıp; Dahili Tıp Bilimleri; Aile Hekimliği; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Family Medicine; Health Sciences; Klinik Tıp (MED); Klinik Tıp; SAĞLIK BAKIM BİLİMLERİ VE HİZMETLERİ; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; HEALTH CARE SCIENCES & SERVICES; MEDICINE, GENERAL & INTERNAL; Tıbbi Terminoloji; Tıbbi Sekreterlik ve Transkripsiyon; Sağlık Bilgi Yönetimi; Sağlık Meslekleri (çeşitli); Genel Sağlık Meslekleri; Gözden Geçirme ve Sınav Hazırlığı; Patofizyoloji; Liderlik ve Yönetim; Temel Bilgi ve Beceriler; Toplum Sağlığı ve Evde Bakım; Bakım Planlaması; Değerlendirme ve Teşhis; Dahiliye; Sağlık Politikaları; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; Medical Terminology; Medical Assisting and Transcription; Health Information Management; Health Professions (miscellaneous); General Health Professions; Review and Exam Preparation; Pathophysiology; Leadership and Management; Fundamentals and Skills; Community and Home Care; Care Planning; Assessment and Diagnosis; Internal Medicine; Health Policy; Family Practice; Medicine (miscellaneous); General Medicine; operational research; continuity of care; diabetes mellitus